Defect-interface engineering in V2O5-modified NiO nanoparticles: Microstrain, oxygen vacancies, and dielectric/AC transport - Macit, Cevher Kursat; Gurgenc, Turan; Ayik, Merve; Gurgenc, Ezgi; Guner, Melek; Aksakal, Bunyamin; Ozkan, Betul Cicek (Elsevier Science Sa, 2026)
Nickel oxide (NiO) is a robust p-type wide-band-gap oxide whose dielectric response and charge transport are highly sensitive to defect chemistry and nanoscale interfacial architecture. Here, V2O5-modified NiO nano-particles were synthesized via a CTAB-assisted sol-gel route using a controlled composition series (0, 1, 2, 3, 5, and 10 wt% V2O5) to establish composition-resolved structure-defect-property correlations. XRD supported by Williamson-Hall analysis reveals a pronounced dopant-driven microstrain buildup and a crossover near 3-5 wt % where strain localization and interface or secondary-phase contributions become increasingly influential. XPS confirms vacancy-enriched near-surface chemistry through the systematic growth of defect-related O 1 s components while preserving the NiO-dominated Ni 2p fingerprint, indicating vacancy-mediated charge compensation rather than a dominant Ni valence transition. Broadband dielectric spectroscopy (1 kHz-10 MHz) shows a systematic enhancement of epsilon' at low frequency, consistent with strengthened Maxwell-Wagner-Sillars interfacial polarization in an increasingly heterogeneous nanograin network. At 1 kHz, epsilon' increases from 8.04 (pristine NiO) to 13.12 (10 wt% V2O5), while tans remains within a narrow range. AC conductivity simultaneously increases from 3.30 & times; 10-8 to 5.71 & times; 10-8 S/cm and follows a strongly dispersive response described by Jonscher-type behavior, supporting defect-assisted localized transport through the Ni-O-V interface landscape. Overall, V2O5 modification emerges as an effective defect-interface engineering strategy for tuning permittivity, loss behavior, and frequency-sensitive transport in NiO-based nanodielectrics, with relevance to high-k dielectric layers, frequency-responsive ceramic components, and interface-controlled energy and sensing architectures.
Keywords: Nickel oxide; Maxwell-wagner-sillars polarization; Dielectric spectroscopy; AC conductivity; Nanocomposites